DETEKSI KETIDAKSEIMBANGAN TEGANGAN PADA TRANSFORMATOR DISTRIBUSI BERBASIS SENSOR PZEM-004T TERNOTIFIKASI BUZZER - Ridho Ariandi; Kartika kartika Kartika (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2022)
Abstract The distribution transformer is part of the distribution system, the transformer that is closest to the customer, if there is a problem with this transformer, the customer will immediately feel it. So to ensure the availability of electricity distribution, this transformer requires periodic maintenance and service. Detection of distribution transformers by detecting an imbalance of voltage and oil temperature in the transformer. To get the voltage and current values using the PZEM-004T sensor and for the transformer oil temperature value with a temperature of DS18B20 which will be forwarded to the LCD screen via the Arduino Uno platform. For the average value of the voltage obtained is 65V. this tool successfully reads the output of current, voltage and transformer oil temperature well with an average error of 0.74% at the maximum current reading in phase T. The system can provide information if there is a voltage imbalance, for voltage imbalance the largest error percentage is obtained. in Phase R of 6.31%. The voltage imbalance should not be more than 2.5% so that the voltage value that is read on the R phase exceeds the capacity of the voltage imbalance which causes a voltage imbalance disturbance in the T phase and the display of the value that is read on the LCD will appear the words